Islamic Humanistic Educational Philosophy: Character-Building Strategies for MTs Students in the 21st Century - Virdatus Sholikhah; Komarudin Sassi (Bulletin of Pedagogical Research, 2025)
Education in the 21st century emphasizes not only cognitive skills but also the holistic development of character. This study explores the philosophy of Islamic humanistic education as a strategic approach to strengthening students’ character in Madrasah Tsanawiyah (MTs). Islamic humanistic philosophy promotes the comprehensive development of human potential by positioning students as active, independent, and responsible agents of learning, while remaining firmly rooted in the values of the Qur’an and Sunnah. Employing a qualitative-descriptive method through a literature review, this study reveals that the implementation of Islamic humanistic principles in MTs can reinforce essential values such as religiosity, empathy, discipline, responsibility, and integrity. Consequently, this approach contributes to nurturing Muslim generations who are adaptive, morally grounded, and well-prepared to face the complex global challenges of the 21st century. This study contributes to the discourse on character education by integrating Islamic humanistic philosophy into contemporary educational frameworks, offering a conceptual model that can guide educators and policymakers in designing value-based learning environments within Islamic schools.